Kualitas Pelayanan Pembayaran Pensiun Pegawai Negeri Sipil (PNS) Pada PT. TASPEN (Persero) Cabang Manado - Langkai, Priskilla G.; Pelleng, Frendy A. O.; Keles, Dantje (Sam Ratulangi University, 2018)
The government gave the task of organizing and managing the pension fund program to PT. TASPEN (Persero). To provide an assessment regarding the quality of services provided to the recipients stated by Zeithhml Parasuraman-Berry (2012). This research was conducted to find out how the quality of services in PT. Taspen (PERSERO) manado. The method used in this research is survey method, research takes samples from the population using questionnaires as a data collection tool. Analytical data using TERRA analysis, which analyzes service quality using the dimensions of tangibles (bukti langsung), (reliability), responsiveness (daya tanggap), assurance (jaminan), emphaty (empati). And with the results obtained, that the highest level of conformity lies in individual attention to employees, which is 96%. While the lowest level of suitability lies in the sense of security given to customers by 83%. From this study shows that the level of appropriateness of service performance is the emphaty (empati) dimension of employee attention with very high customer expections. On the contrary, the state of safety is the level of suitability is low. It indicates that a sense of security is not in accordance with customer expectation which means that customers feel a sense of security is enhanced by PT. Taspen. Then from the five dimensions of service quality namely tangible, emphaty, reliability, responsiveness, assurance, obtained result of S (satisfaction) or satisfaction is S <1. The result of the analysis show the fact that the compatibility service performance (kesesuaian antara kinerja) and service/customer (layanan pelanggan) has not reached the maximum level of satisfaction. Based n these facts, it can be seen that customers have not been fully satisfied with the service provided by employees of PT. Taspen.Keywords: Service Performance, Costumer Expectation